Функции интертекстуальности в повести А. Гаврилова «Вопль впередсмотрящего» - Шеховцова, Т.А. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2012)
В статье рассматриваются интертекстуальные связи и функции интертекста в повести А. Гаврилова «Вопль впередсмотрящего». Показано, что интертекстуальные отсылки существенно проясняют авторскую концепцию и ее генезис, усиливают экзистенциальное содержание, акцентируют эсхатологическую проблематику, достраивают образ повествователя. Претексты образуют единое смысловое поле, организуемое сквозными мотивами и составляющее второй содержательный план повести. In the article the intertextual connections and the functions of intertext in A.Gavrilov's story “А lookout’s cry” are considered. It is shown that intertextual refferences essentially clarify the author's concept and its genesis, intensify the existential content, emphasize the eschatological problematics, and complete the image of the storyteller. The pretexts form a common semantic field organized by prevailing motives; this field composes the second substantial plan of the story.
The functions of intertextuality in A.Gavrilov's story “А lookout’s cry”
Шеховцова Тетяна Анатоліївна, докт. філол. наук, професор кафедри історії російської літератури Харківського національного університету імені В. Н. Каразіна.
Keywords: интертекст; интертекстуальность; экзистенциальное содержание; эсхатологические мотивы; intertext; intertextuality; existential content; eschatological motives